T Helper 17 Cells in Autoimmune Liver Diseases - Masanori Abe; Yoichi Hiasa; Morikazu Onji (Clinical and Developmental Immunology)
Many autoimmune diseases are driven by self-reactive T helper (Th) cells. A new population of effector CD4+ T cells characterized by the secretion of interleukin (IL)-17, referred to as Th17 cells, has been demonstrated to be phenotypically, functionally, and developmentally distinct from Th1 and Th2 cells. Because the liver is known to be an important source of transforming growth factor-β and IL-6, which are cytokines that are crucial for Th17 differentiation, it is very likely that Th17 cells contribute to liver inflammation and autoimmunity. In contrast, another distinct subset of T cells, regulatory T cells (Treg), downregulate immune responses and play an important role in maintaining self-tolerance. In addition, there is a reciprocal relationship between Th17 cells and Tregs, in development and effector functions, and the balance between Th17 and Treg cells can affect the outcome of immune responses, particularly in autoimmune diseases. In this review, we will focus on the latest investigative findings related to Th17 cells in autoimmune liver disease.